Variations in plasma phytoestrogen concentrations in European adults. - Peeters, P; Slimani, N; van der Schouw, Y; Grace, P; Navarro, C; Tjonneland, A; Olsen, A; Clavel-Chapelon, F; Touillaud, M; Boutron-Ruault, M; Jenab, M; Kaaks, R; et al. (2007)
Dietary phytoestrogens may play a role in chronic disease occurrence. The aim of our study was to assess the variability of plasma concentrations in European populations. We included 15 geographical regions in 9 European countries (Denmark, France, Germany, Greece, Italy, Spain, Sweden, The Netherlands, and UK) and a 16th region, Oxford, UK, where participants were recruited from among vegans and vegetarians. All subjects were participants of the European Prospective Investigation into Cancer and Nutrition (EPIC). Plasma concentrations of 3 isoflavones (daidzein, genistein, and glycitein), 2 metabolites of daidzein [O-desmethylangolensin (O-DMA) and equol] and 2 mammalian lignans (enterodiol and enterolactone) were measured in 1414 participants. We computed geometric means for each region and used multivariate regression analysis to assess the influence of region, adjusted for gender, age, BMI, alcohol intake, smoking status, and laboratory batch. Many subjects had concentrations below the detection limit [0.1 microg/L (0.4 nmol/L)] for glycitein (80%), O-DMA (73%) and equol (62%). Excluding subjects from Oxford, UK, the highest concentrations of isoflavones were in subjects from the Netherlands and Cambridge, UK [2-6 microg/L (7-24 nmol/L); P < 0.05], whereas concentrations for lignans were highest in Denmark [8 microg/L (27 nmol/L); P < 0.05]. Isoflavones varied 8- to 13-fold, whereas lignans varied 4-fold. In the vegetarian/vegan cohort of Oxford, concentrations of isoflavones were 5-50 times higher than in nonvegetarian regions. Region was the most important determinant of plasma concentrations for all 7 phytoestrogens. Despite the fact that plasma concentrations of phytoestrogens in Europe were low compared with Asian populations, they varied substantially among subjects from the 16 different regions.